Pengembangan Website untuk Pembaruan Media Informasi dan Promosi FJ Studio Bandung dengan memanfaatkan Google Sites - Gia Septiana Wulandari; Mahmud Dwi Sulistiyo; Febryanti Sthevanie (I-Com: Indonesian Community Journal, 2024)
FJ Studio is a women's fitness studio located in Bandung. The problem is, since its establishment in 2018, FJ Studio has relied solely on word-of-mouth promotion and through the Instagram account of a local influencer. The promotional methods used are deemed ineffective; furthermore, the cost of the influencer is considered high. Therefore, to make FJ Studio's promotions more effective and cost-efficient, we, as a community service team from the Faculty of Informatics, Telkom University, developed a website to serve as an informational and promotional platform for FJ Studio. Due to the limited personnel at FJ Studio, ease of website management was prioritized. We utilized the Google Sites framework for the development of the FJ Studio website, which can be easily managed online and offers various practical and user-friendly content management features. We conducted training sessions for the owners and staff of FJ Studio to introduce them to the website management environment so that they can use and update it regularly.